Bamboo for Pan India Plantation Programmes - Preliminary Observations from Recent Trials - Haridasan, K.; Tewari, Salil (Indian Forester, 2008)
National Bamboo Mission envisages bamboo plantations over more than 1.7 ha which will need more than 7 crore plants. It is not enough to rely upon seedlings alone to meet this requirement and several organizations have started experimenting propagation by vegetative methods. These experiments have not finally concluded, but trends noticed in them can be predicted to some extent. Besides new techniques and machinery have also to be evaluated. Basing on these trends of bamboo have also to the evaluated. Basing on these trends seven bamboo species which include Bambusa balcooa, B. bambos, B. nutans etc. have been identified for pan Indian large scale plantations while 8 other species which include Dendrocalamus asper, Phylostachys pubescens, Guadua angustifolia etc. can be tried for regional plantation.